Some aspects of formation and classification of free economic zones (Journal of Economic Research & Business Administration, 2015)
In this article various interpretation of the concept "free economic zone" (further – SEZ) are considered. Characteristics of formation and SEZ functioning are analyzed, need of functioning of these or those types of SEZ is revealed and proved. Definite purposes of creation of SEZ the comparative analysis of SEZ proceeding from the purposes of their creation and economic feasibility for the country also is carried out. Classification of SEZ by the main directions of their activity taking into account functional components of such zones is given. The accounting of specifics of the SEZ different groups and the organizations functioning in their territory will allow to improve state regulation of special economic zones, and also management of them on places.
Keywords: free economic zone; special economic zone; territory of priority development; classification of free economic zones